Knowledge Management in Composition of Construction Contracts - Eva Trinkūnienė; Vaidotas Trinkūnas (Entrepreneurial Business and Economics Review, 2015)
The objective of this paper is to present a model which will allow knowledge management in construction contracts composition. It was decided to investigate the possibilities to manage knowledge in constructions contracts composition. The complexity of construction process interested parties, construction contract life cycle, multilayer construction contracts modelling possibilities were evaluated.Â In the following research, model of information system for construction contracts structural analysis (previously developed by the authors) is additionally developed by taking into consideration the possibility to use the knowledge management.